Prevalencia de brucelosis bovina en los centros de faenamientos de los cantones Chone y Portoviejo y sus buenas prácticas sanitarias - Ponce Guzmán, Josselyn Alexandra (2021)
The objective of the research was to determine the prevalence of bovine brucellosis and the application of good sanitary practices in slaughter centers of the Chone and Portoviejo cantons of the Manabí province, by means of the Rosa de Bengala agglutination serological test. For this work, 108 blood samples were taken from animals that were for slaughter in the Chone canton and 237 blood samples from animals in the Portoviejo canton with a total of 345 samples. The puncture was carried out in the neck just where the jugular vein can be seen, for this, 18 x 1 ”25 mm needles were used, the collected samples were labeled and packed in coolers, protecting their integrity, then sent to the“ ANIMALAB ”Laboratory, The same person who issued the results of 236 negative tests and 1 positive in the city of Portoviejo, that is, 0.42% of the total that is at an age of 4 years, which raised the alert and the relevance of this investigation and 108 negative tests in the City of Chone. It is concluded that the prevalence of brucellosis in the Portoviejo slaughterhouse is low with 0.42%. Therefore, it was determined that in the slaughterhouse of the canton of Portoviejo 90% do know the Laws and animal health and in the slaughterhouse of the Canton Chone 79% do not know the Laws of Animal Health.